Acute heat shock leads to cortical domain internalization and polarity loss in the C. elegans embryo. Issue 4 (29th March 2016) - Singh, Deepika; Odedra, Devang; Lehmann, Christina; Pohl, Christian
Summary: Many developmental processes are inherently robust due to network organization of the participating factors and functional redundancy. The heterogeneity of the factors involved and their connectivity puts these processes at risk of abrupt system collapse under stress. The polarization of the one‐cell C. elegans embryo constitutes such an inherently robust process with functional redundancy. However, how polarization is affected by acute stress has not been thoroughly investigated. Here, we report that heat shock (34°C, 1 h) triggers a highly reproducible loss of the anterior and collapse of the posterior polarity domains. Temperature‐dependent loss of cortical non‐muscle myosin II drastically reduces cortical tension and leads to internalization of large plasma membrane domains including the membrane‐associated polarity factor PAR‐2. After internalization, plasma membrane vesicles and associated factors cluster around centrosomes and are thereby withdrawn from the polarization process. Transient formation of the posterior polarity domain suggests that microtubule‐induced self‐organization of this domain is not compromised after heat shock. Hence, our data uncover that the polarization system undergoes a temperature‐dependent collapse under acute stress. genesis, 2016. © 2016 Wiley Periodicals, Inc. genesis 54:220–228, 2016. © 2016 Wiley Periodicals, Inc.